2011
DOI: 10.1007/s00264-011-1414-4
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of the spine. A systematic review of case series

Abstract: Purpose The objective of this systematic review was to characterise the methodological issues, as well as clinical, diagnosis, microbiological and treatment characteristics of patients with spinal tuberculosis. Methods We conducted a systematic review including prospective or retrospective case series written in English,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
104
0
24

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 49 publications
(38 reference statements)
10
104
0
24
Order By: Relevance
“…These data are very similar to the data reported by Song et al 5 and Ansari et al 10 The anatomical regions most affected in this study were the thoracic and lumbar regions; however, Rasouli et al, 12 Pu et al 13 and Fuentes et al 15 report that the most affected region is the thoracic region, as it is closer to the pulmonary region. The existence of two or more vertebrae affected by the tuberculosis is frequent, the most commonly affected vertebral bodies being L3 and L4.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These data are very similar to the data reported by Song et al 5 and Ansari et al 10 The anatomical regions most affected in this study were the thoracic and lumbar regions; however, Rasouli et al, 12 Pu et al 13 and Fuentes et al 15 report that the most affected region is the thoracic region, as it is closer to the pulmonary region. The existence of two or more vertebrae affected by the tuberculosis is frequent, the most commonly affected vertebral bodies being L3 and L4.…”
Section: Discussionsupporting
confidence: 71%
“…The existence of two or more vertebrae affected by the tuberculosis is frequent, the most commonly affected vertebral bodies being L3 and L4. 12,13,15 Most patients were diagnosed during the first year of evolution of the disease. This is consistent with some studies such as those of Ansariy et al 10 and Moon et al, 16 who state that tuberculosis of spine is frequently reported from the first year of evolution, with a history of incidents of low back pain, sometimes accompanied by other symptoms such as loss of appetite, weight loss, or sweating, as symptoms with insidious onset.…”
Section: Discussionmentioning
confidence: 99%
“…En la fase sintomática de la espondilitis tuberculosa, los síntomas son insidiosos e inicialmente inespecíficos; el malestar, la fiebre, la pérdida de apetito y de peso, así como la diaforesis nocturna, se presentan en alrededor de 20 a 30 % de los casos. La historia natural de la enfermedad puede extenderse a lo largo de meses o años, con un rango promedio de 4 a 11 meses (13). En el caso que se presenta aquí, transcurrieron cinco meses desde el inicio de los síntomas hasta la primera consulta y cerca de 18 hasta el diagnóstico exacto.…”
Section: Discussionunclassified
“…1,4,6,9,11 Many of these patients are bed-bound due to paraplegia, requiring prolonged in-hospital stay and extended rehabilitation at an appropriate facility. This places an additional burden on an already strained health care system.…”
Section: Discussionmentioning
confidence: 99%